A imaginação de Palácio e a mediação das imagens da cidade na educação infantil de Vitória - Ferreira, Sonia Maria de Oliveira (2011)
This research relates to image reading in kindergarten, presenting as theoretical referential the contributions by Vygotsky, Sarmento, Schultz-Foerster, Araujo and others. It is characterized as empirical research, using the qualitative approach, with data collected through semi-structured interviews, oral narratives and imagery of children, photographs and footage of the activities undertaken at school and beyond. It emphasizes the importance of educational practices in the exhibition spaces and the unveiling of the imagination, having children, the arts teacher, trainers and teachers / educators as subjects of teaching and learning process. The objective is to analyze the imaginary drawings of palaces built by children from the kindergarten, in order to understand how speeches may be mediated by pictorial images of the city. Soon, they realized that, through drawings / pictorial records, reassembled scenes from his imagination through the concept of the palace and created others (own) after the visit / tour of the city. Thus, children represent their own views of the world, as heard and seen